Perancangan Nomor Spare Part dan Pengendalian Persediaan Gudang Spare Part di PT X - Monica Yunita; Herry Christian Palit (Jurnal Titra, 2020)
PT X is company that produces products from palm oil. The production process is carried out using a machine. Spare parts are provided by the spare parts warehouse. Currently, the material number of spare parts consists of 6 random numbers. New material numbers are created using the group technology approach to simplify identification of spare parts. New material number consists of 12 numbers, 4 numbers for machine codes, 3 numbers for component group codes, 2 numbers for component type codes, and 3 numbers for spare part codes. Inventory control in the spare part warehouse is also inefficient. New inventory control are created using periodic review method. Inventory control with a service level of 95% for class A and class B, results in 8.64% cost savings with 4 types of stockout items. Changing the service level 78% in class B results in 15.9% cost savings with 9 types of stockout items.